2022
DOI: 10.1155/2022/1023865
|View full text |Cite|
|
Sign up to set email alerts
|

The Development and Realization of Digital Panorama Media Technology Based on VR Technology

Abstract: The purpose of this paper is to understand the digital 3D multimedia panoramic visual communication technology based on virtual reality. Firstly, the key concepts and characteristics of virtual reality are introduced, including the development and application of digital three-dimensional panorama technology. Then, according to the theoretical research, some basic knowledge of 3D panoramic image Mosaic is introduced, including camera image modeling, image sharing, and image exchange. Finally, with the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Virtual reality technology, three-dimensional (3D) photography, spherical images, or simulated real-world [1], [2] are computer-generated media that are real scenes and have a coverage of 360° [3], [4]. Interactivity, immersion, and imagery are the main features of virtual reality that differentiate it from other technologies [5].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality technology, three-dimensional (3D) photography, spherical images, or simulated real-world [1], [2] are computer-generated media that are real scenes and have a coverage of 360° [3], [4]. Interactivity, immersion, and imagery are the main features of virtual reality that differentiate it from other technologies [5].…”
Section: Introductionmentioning
confidence: 99%
“…VLEs can replicate physical environments in 360° panoramic images which utilize digital cameras to shoot the real physical environment. This enables manipulation of the viewpoint within digital displays in all directions around the vertical axis (Qiu & Tao, 2022). The panoramic VR facilitates a sense of presence within the VLE, allowing interactivity and the ability to roam the environment with 3 degrees-of-freedom (around rotational axes).…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%